Detection of post-traumatic abdominal pseudoaneurysms by CEUS and CT: A prospective comparative global study (the PseAn study)—study protocol - Virdis, Francesco; Cioffi, Stefano Piero Bernardo; Abu-Zidan, Fikri; Reitano, Elisa; Podda, Mauro; Altomare, Michele; Spota, Andrea; Bini, Roberto; Kumar, Jayant; Chiara, Osvaldo; Cimbanassi, Stefania (Frontiers in Surgery, 2023)
The success of non-operative management in trauma increased with the availability of new-generation CT scan machines, endoscopy, and angiography, becoming the standard of care in hemodynamically stable trauma patients with abdominal solid organ injuries, with a success rate of 78% to 98%. Post-traumatic pseudoaneurysms (PAs) can develop at any region of an injured artery and they may cause delayed bleeding in splenic or hepatic trauma, with an incidence in patients treated with NOM of 2–27% and 1.2-6.1% respectively. Diagnosis is made by angiography, contrast-enhanced computer tomography (CT), or Doppler Ultrasound (US) while the use of the contrast-enhanced ultrasound (CEUS), has increased in recent years although few data are available about CEUS feasibility in the follow-up setting. The PseaAn study has been designed to assess the role of CEUS in the follow-up of abdominal trauma by defining its sensitivity, specificity and predictive values compared with abdominal CT scan. The PseAn study is a multi-centric international diagnostic cross-sectional study initiated by the Level I Trauma Center of the Niguarda Ca’ Granda Hospital in Milan, Italy. Institutions are recruited internationally. To study the role of CEUS in detecting post-traumatic splenic, hepatic, and renal PAs compared with the gold standard of CT with intravenous contrast at different follow-up time points, and whether it can replace CT scan in the follow-up of solid organ injuries, patients with OIS III and above will undergo a follow-up with both a CEUS and CT scan to detect post-traumatic parenchymal pseudoaneurysm within two to five days from injury. The use of CEUS in the follow-up of abdominal trauma follow-up (particularly blunt trauma) has increased, to minimize the use of ionizing radiation and contrast media and encouraging results have been published during the last decade showing that CEUS is an accurate technique for evaluating traumatic lesions of solid abdominal organs. Conclusions We think that CEUS, which is underused worldwide, is a useful and safe tool that may replace CT scan in follow-up with the major advantage of reduced radiation. Our current study may give stronger evidence to support this view ClinicalTrial.Gov ID: NTC05627908